The Rise of Broadband as an Essential Utility and Emergent Concepts in Universal Access in Advanced Economies: Perspectives from Canada - Reza Rajabiun (International Telecommunications Society (ITS), 2017)
This article investigates how the transition of broadband Internet connectivity to an essential utility has influenced the development of universal access objectives and policies in Canada. In order to better understand the interplay between economic reality of broadband as an essential social and business input and the policymaking process, the article utilize Natural Language Processing (NLP) tools to map conceptual emphasis in the content of submissions by stakeholders to the telecom regulator in proceedings to review Canada's universal access policy framework between 2009-2016. The analysis documents that increasing essentiality of broadband Internet access services as an enabler of social and economic activities makes their quality and affordability problems with general economic and policy relevance that cross the traditional conceptualization of universal access in terms of the rural-urban digital divide.
Keywords: 330